2011
DOI: 10.1007/s00426-011-0380-1
|View full text |Cite
|
Sign up to set email alerts
|

Observing how others lift light or heavy objects: time-dependent encoding of grip force in the primary motor cortex

Abstract: During movement observation, corticomotor excitability of the observer's primary motor cortex (M1) is modulated according to the force requirements of the observed action. Here, we explored the time course of observation-induced force encoding. Force-related changes in M1-excitability were assessed by delivering transcranial magnetic stimulations at distinct temporal phases of an observed reach-grasp-lift action. Temporal changes in force-related electromyographic activity were also assessed during active move… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 58 publications
2
41
0
Order By: Relevance
“…TMS studies on movement observation have shown that the observed movement-related effort modulates CSE in a transitive reach-grasp-lifting task (Alaerts et al, 2010(Alaerts et al, , 2012. Within this framework, we found a significant difference between the observation of an effort-related movement and a VC condition.…”
Section: The Effect Of Movement Effort On Csementioning
confidence: 43%
“…TMS studies on movement observation have shown that the observed movement-related effort modulates CSE in a transitive reach-grasp-lifting task (Alaerts et al, 2010(Alaerts et al, , 2012. Within this framework, we found a significant difference between the observation of an effort-related movement and a VC condition.…”
Section: The Effect Of Movement Effort On Csementioning
confidence: 43%
“…Our findings argue for the inclusion of observed kinematic information from prior lifts (evidently a reliable source of possible weight information for the sensorimotor system in this simple model). In support of this idea, (Alaerts et al, 2011) have shown that, in a blocked design, visual information about object weight from previously observed lifts drives cortico-spinal excitability before visual information about object weight in an upcoming observed lift is available. These low-level modulations may even serve a behavioural function, given the growing experimental evidence for a link between cortico-spinal excitability and motor output (Bagce et al, 2013;Klein-Flügge et al, 2013;Orban de Xivry et al, 2013).…”
Section: Discussionmentioning
confidence: 86%
“…we hope to explicitly test this prediction in future research by measuring lifting behaviour and cortico-spinal excitability at various time points throughout montages of observed lifts, when only a fraction of the kinematic error information is available (cf. Alaerts et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Another pertinent experiment that highlights the role of the motor system for action prediction is reported by Alaerts, de Beukelaar, Swinnen, and Wenderoth (2011). Using transcranial magnetic stimulations, the authors explored how the excitability of the observer's primary motor cortex (M1) changes according to the forcerequirements of an observed action.…”
mentioning
confidence: 99%